Peran Ekspatriat Dalam Transfer Pengetahuan Pada Perusahaan Multinasional: A Systematic Literature Review - Zata Yumni Subhati Nursabrina; Madziatul Churiyah; Arief Npviarakhman Zagladi (Universitas Muhammadiyah Metro, 2025)
The purpose of this SLR research is to determine the role of expatriates in knowledge transfer in multinational companies. The research method used is systematic literature observation using the Preferred Reporting Item Method for Systematic Review and Meta-analysis (PRISMA), data sources obtained from Google Science direct and Emerald from 2019-2024, obtained 241 journals. The journals were re-selected, the results: 45 journals out of 241 journals that can be accessed. Then based on the title, 10 journals were obtained. The results showed that knowledge transfer (KT) from expatriates tends to have a role in strengthening the core competencies that already exist in the company. Knowledge from expatriates plays a role in filling the knowledge gaps of individuals/teams as a companion to expatriates. Supported by the expertise and knowledge already possessed, local personnel can increase their capabilities and capacities, so that the accumulation can form individual/team competencies. keywords : expatriates, knowledge transfer, mnc